Effect of Treated Wastewater Irrigation on Heavy Metals Distribution in a Tunisian Soil - Khaskhoussy, K.; Kahlaoui, B.; Messoudi Nefzi, B.; Jozdan, O.; Dakheel, A.; Hachicha, M. (Engineering, Technology & Applied Science Research, 2015)
Treated wastewater (TWW) may contain toxic chemical constituents that pose negative environmental and health impacts. In this study, soil samples under treated wastewater irrigation were studied. For this purpose, six plots were made in an irrigated area in north of Tunisia and treated with two water qualities: fresh water (FW) and treated wastewater (TWW). Five soil depths were used: 0-30, 30-60, 60-90, 90-120 and 120-150 cm. The TWW irrigation increased significantly (P≤0.05) the soils’ EC, Na, K, Ca, Mg, Cl, SAR, Cu, Cd and Ni and had no significant (P ≤0.05) effect on the soils’ pH, Zn, Co and Pb contents. EC, Na, Cl, SAR, Zn and Co increased significantly with soil depth. The results for K, Ca, Mg, Cd, Pb and Ni exhibited similar repartition in different layers of soil. It was also shown that the amount of different elements in soil irrigated with fresh water (FW) were less compared with the control soil.